A Penguatan Minat dan Ketrampilan Masyarakat Desa Wisata dalam Era Industry4.0 dan Society5.0 - Witarsana , Agung Gede; Diwyarthi, Ni Desak Made Santi; Wiartha, Nyoman Gede Mas Wiartha; Suastini, Ni Made; Sadjuni , Ni Luh Gede Sri; Sulistyawati, Ni Luh Ketut Sri; Sabudi, I Nyoman Sukana (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
The Community Service Activity by the Hospitality Management Program, Bali Tourism Polytechnic, held on Saturday, May 27, 2023, was conducted through training and hands-on practice for 25 MSME owners in Cemagi Tourism Village. With the theme 'Strengthening the Interests and Skills of the Residents of Cemagi Tourism Village,' this activity has had a positive impact in preparing the community to participate in the era of Industry 4.0 and Society 5.0. The development of tourism and the skills of the local community are key to improving the well-being and economic potential of Cemagi Tourism Village. The choice to focus on strengthening interests and skills as baristas was a wise decision, considering the growth of restaurants and accommodations in Badung Regency that require skilled workers in the coffee shop industry.